Central metabolism as a potential origin of sex differences in morphine antinociception but not induction of antinociceptive tolerance in mice. (8th February 2022) - Gabel, Florian; Hovhannisyan, Volodya; Andry, Virginie; Goumon, Yannick
Abstract : Background and Purpose: In rodents, morphine antinociception is influenced by sex. However, conflicting results have been reported regarding the interaction between sex and morphine antinociceptive tolerance. Morphine is metabolised in the liver and brain into morphine‐3‐glucuronide (M3G). Sex differences in morphine metabolism and differential metabolic adaptations during tolerance development might contribute to behavioural discrepancies. This article investigates the differences in peripheral and central morphine metabolism after acute and chronic morphine treatment in male and female mice. Experimental Approach: Sex differences in morphine antinociception and tolerance were assessed using the tail‐immersion test. After acute and chronic morphine treatment, morphine and M3G metabolic kinetics in the blood were evaluated using LC‐MS/MS. They were also quantified in several CNS regions. Finally, the blood–brain barrier (BBB) permeability of M3G was assessed in male and female mice. Key Results: This study demonstrated that female mice showed weaker morphine antinociception and faster induction of tolerance than males. Additionally, female mice showed higher levels of M3G in the blood and in several pain‐related CNS regions than male mice, whereas lower levels of morphine were observed in these regions. M3G brain/blood ratios after injection of M3G indicated no sex differences in M3G BBB permeability, and these ratios were lower than those obtained after injection of morphine. Conclusion: These differences are attributable mainly to morphine central metabolism, which differed between males and females in pain‐related CNS regions, consistent with weaker morphine antinociceptive effects in females. However, the role of morphine metabolism in antinociceptive tolerance seemed limited. LINKED ARTICLES: This article is part of a themed issue on Advances in Opioid Pharmacology at the Time of the Opioid Epidemic. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v180.7/issuetoc